Analisis Pengaruh E- Wom Terhadap Keputusan Pembelian Mahasiswa/i dari Aplikasi Tiktok Shop - Novina Veronica; Yuliana; Weny (Journal of Trends Economics and Accounting Research, 2023)
The aim of this research is to determine the influence of word of mouth promotion (E-WOM) on consumer purchasing decisions from the Tiktok Shop application. The method used in this research is descriptive method, this type of research is quantitative data, primary data obtained through questionnaires. The research population that will be used in this research is all students of Cendana Polytechnic. Sampling was carried out on 100 research samples. The analysis technique used is simple linear analysis and statistical tests, namely t-test (partial) using SPSS (statistical package for the social sciences) software. The test results show that Word of Mouth Promotion partially has a positive and significant effect on consumer purchasing decisions at the TikTok Shop.